Compost Effects on Soil Nutritional Quality and Pepper (Capsicum annuum L.) Yield - Melis Cercioglu (Journal of Agricultural Sciences)
There is a large amount of organic waste depending on the climatic conditions and product diversity in the agricultural areas of Turkey. These wastes can be used as a soil conditioner to reduce environmental problems and enrich soil organic matter by the transformation of organic wastes into organic manure with the process of composting. This study was performed to investigate the effects of composted greenhouse wastes (tomato residues) and animal manure on macro nutrient contents of soil and green pepper yield. Treatments were as follows: (1) Control, (2) mineral fertilizer, (3) 40 t ha-1 animal manure, (4) 40 t ha-1 animal manure + mineral fertilizer, (5) 40 t ha-1 tomato residuals, (6) 40 t ha-1 tomato residuals + mineral fertilizer, (7) 80 t ha-1 tomato residuals, (8) 80 t ha-1 tomato residuals + mineral fertilizer. Three replicates each of disturbed soil samples (two sampling) were collected (0-20 cm) from each treatment in two vegetation period and green pepper was used as a test plant in the study. In consequence of the research, significant increases were observed in crop yield and macro nutrient contents of soil. The highest increasing rate was analyzed in yield values as 305%. The most effective treatments on soil macro nutrient content and yield were determined as 40 t ha-1 animal manure combined with mineral fertilizer and 80 t ha-1 composted tomato residues combined with mineral fertilizer.